Meningkatkan Hasil Belajar Matematika Materi Penjumlahan dengan Mengunakan Media Pohon Pintar Pada Siswa Kelas 1 SDK Wegoknatar - Theresia Ardila Keitimu; Lukas Bera; Maria Angelina Fransiska Mbari (Journal on Education, 2023)
This study aimend to improve the learning Outcomes of addition material using smart tree media for 1students at SDK wegoknatar. This research employed clasroom action research ( CAR) which was designed to help teacher ( recearchers) in dinding and solving learning problems that occur in the classroom.This clasroom action research was conducted in cycles, between cycle 1 and 11. The pacticipants were 12 students. The results of the study indicated that after giving action for two cycles the average score of the test result of improving learning Outcomes in addition material using smart tree media in Mathematics subject had increased. The first meeting of the cycle 1 resulted in a score of 45%, and the second meeting 55% meaning that not yet reached the KKM. In the first meeting of cycle ll, there was an increase in value of 65%, and at the second meeting 95%. Thus, the learning Outcomes from cycle ll increased and were includded in the very good category or fulfilled the KKM. This indicated that improving learning Outcomes in Mathematic addition material by using smart tree media could be further applied to improve student learning achievement, especially in the mathematics subject.